The Influence of ISO 9001: 2015 Quality Management System Implementation on Marketing Performance at PT Timah Tbk - Wiyono; Silitonga, Roland Y. H.; Heryanto, Dhany (Journal of Management Studies and Development, 2025)
This study evaluates how implementing the ISO 9001:2015 Quality Management System affects marketing performance and product quality at PT Timah Tbk. The company faced production fluctuations in 2023, leading to a sharp revenue decline and significant losses. Using a quantitative descriptive approach with a survey method, the research analyzes data from employees and management. The findings show that ISO 9001:2015 implementation positively impacts product quality (path coefficient = 0.9867) and quality management (path coefficient = 0.9036). The R-Square value indicates that ISO 9001:2015 explains 81.64% of product quality improvements, while product quality accounts for 97.38% of marketing performance changes. These results suggest that effective quality management through ISO 9001:2015 enhances marketing efficiency and strengthens customer trust, helping the company navigate competition in the tin industry.